Effect of B-carotene on Serum Progesterone Level in Dairy Heifers - BARUAH, S N; GOSWAMI, B C (The Indian Journal of Animal Reproduction, 2023)
Twenty crossbred heifers in the age group of 2-3.5 years and body varying from 130 to 190 Kg were used in the study. All the· heifers were kept on a 8-carotene free basic ration consisting of concentrate, @ 3 Kg per heifer per day and paddy straw, adlibitum. Each heifer in the control group received a daily supplement of 60,000 1.U. vitamin A in their feed while in the experimental group each heifer was given 20,000 1.U: vitamin A plus 100 mg 8-Carotene daily. The heifers of the experimental group had a significantly higher level of 8-carotene than the control group throughout the period of the experiment. It was observed that, although not statistically significant, the blood progesterone level during oestrous cycle was apparantly higher in the heifers of the experimental group than that of the control group. But it was significantly higher during pregnancy in the heifers of the experimental group. Higher precentage (75%)- of the experimental heifers had large sized corpus luteum.